Evidence of Self‐Aggregation of Cationic Surfactants in a Choline Chloride+Glycerol Deep Eutectic Solvent. Issue 12 (16th June 2015) - Pal, Mahi; Singh, Ranjan K.; Pandey, Siddharth
Abstract Based on fluorescence probe, electrical conductivity, surface tension, small‐angle X‐ray/dynamic light scattering, and transmission electron microscopy experiments, we present the first clear lines of evidence for self‐aggregation of cationic surfactants of the n‐alkyltrimethylammonium family within an archetypical deep eutectic solvent comprised of a 1:2 molar mixture of choline chloride and glycerol. Estimated thermodynamic parameters suggest this self‐aggregation process to be less entropically driven than that in water. These novel water‐free self‐assemblies might serve as dynamic soft templates to direct the growth of size‐ or shape‐tailored nanoparticles within water‐restricted media.